Туристичні маршрути національних природних парків Волинської області - Міщенко, Олена Віталіївна; Mishchenko, Olena V. (Тернопільський національний педагогічний університет імені Володимира Гнатюка, 2014)
Обґрунтовано передумови формування мережі туристичних маршрутів у національних парках Волинської області. Подано аналіз і характеристику туристичних маршрутів Шацького НПП, НПП “Прип’ять-Стохід”, НПП “Цуманська Пуща”. У Шацькому національному природному парку розроблені туристичні маршрути частково марковані й мають технічне забезпечення. В умовах НПП “Прип’ять-Стохід” найбільш використовувані водні маршрути, частково веломаршрути. НПП “Цуманська Пуща” визначається екстенсивним туристичним осовоєнням, що пояснюється відсутністю адміністрації парку й проведеного функціонального зонування.

Preconditions of development of a network of tourist routes in national natural parks of the Volyn region are proved. The analysis and the characteristic of tourist routes of Shatsky NNP, NNP Pripyat-Stohid, NNP the Tsuman Dense forest is submitted. The Shatsky national natural park has high natural recreational potential ‒ the area that is occupied by water reaches 14,1 %, the total length of a hydrographic network ‒ 1,94 km / km2, percentage of forest land ‒ 56 %, attractive natural conditions among which lake-marsh grounds, meadow and the large forests, the rich world of fauna (especially avifauna) and flora, two marked ecological tracks, a network of bicycle, foot, water routes have allowed to create intensive tourist development. In NNP "Pripyat-Stohid" are high indicators of natural recreational potential, in particular the area that is occupied by water reaches 6 %, total length of a hydrographic network ‒ reaches 2,56 km / km2, percentage of forest land ‒ 35 % that has allowed to generate interesting water routes in this territory. The most known among tourists are “the Magic world of Polesye” and “Pripjat voyage”. However, through absence of a network of recreational establishments that in turn minimises tourist activity, there are signs of extensive tourist development of this territory. In national natural park “Tsuman Dense forest” the administration of park, which would take on itself responsibility of recreational and reserved wildlife management of this territory, is not created. Considering natural features of park, in particular files of deciduous and pine- deciduous woods here, it is expedient to create the foot routes, and in the long term with development infrastructural park maintenance ‒ the bicycle and horse routes.
Tourist routes of national natural parks of the Volyn region
Keywords: національний природний парк; туристичний маршрут; екологічна стежка; екстенсивне, інтенсивне туристичне освоєння; national natural park; a tourist route; an ecological track; extensive, intensive tourist development